Anatomical differences of the cervical esophagus in brachycephalic dogs - Santos, T.I. [UNESP]; Guerra, D.M.L. [UNESP]; Santos, G.V.C. [UNESP]; Doiche, D.P. [UNESP]; Oliveira, F.S. [UNESP] (Elsevier, 2025)
This study investigated anatomical variations of the cervical esophagus in brachycephalic dogs (n=16 Shih Tzus/French Bulldogs) compared to mesocephalic controls (n=16 mixed-breed) through cadaveric dissection. Results revealed that 93.75% of brachycephalic dogs exhibited ventral esophageal sacculation, with 100% prevalence in French Bulldogs versus 92.3% in Shih Tzus. The esophagus showed abnormal ventral/lateral positioning at the thoracic inlet, overlapping the trachea (93.75% of cases) and obscuring its left lateral view, contrasting with mesocephalic anatomy. These alterations correlate with literature reports of esophageal dysfunction in brachycephalic breeds, including reflux (67.39% prevalence in CT studies) and hiatal herniation. The findings suggest that extreme craniofacial conformation exacerbates anatomical deviations, potentially contributing to clinical complications like dysphagia and aspiration. Surgical implications include modified approaches for airway procedures due to altered vascular relationships (left common carotid artery proximity) and esophageal fragility. Limitations include sample bias toward Shih Tzus (81.25%). This study highlights the need for breed-specific anatomical assessments in clinical/surgical management of brachycephalic dogs.